2022
DOI: 10.1186/s41687-022-00509-z
|View full text |Cite
|
Sign up to set email alerts
|

Electronic patient-reported outcomes (e-PROMs) in palliative cancer care: a scoping review

Abstract: Background In palliative oncology settings, electronic patient-reported outcome (PRO) assessment can play an important role in supporting clinical activities for clinicians and patients. This scoping review aims to map the technological innovation of electronic patient-reported outcome measures (e-PROMs) in cancer palliative care and how PRO data collected through e-PROMs can influence the monitoring and management of symptoms and enable better communication between health professionals and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…PC, smartphone or tablet), providing clinicians and researchers with a flexible platform for viewing PROM data 110,111 . Patients suffering from cancer and chronic kidney disease, for instance, have reported that an ePROM platform is a beneficial tool that improves their outcomes 112,113 …”
Section: Future Directions For Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…PC, smartphone or tablet), providing clinicians and researchers with a flexible platform for viewing PROM data 110,111 . Patients suffering from cancer and chronic kidney disease, for instance, have reported that an ePROM platform is a beneficial tool that improves their outcomes 112,113 …”
Section: Future Directions For Researchmentioning
confidence: 99%
“…110,111 Patients suffering from cancer and chronic kidney disease, for instance, have reported that an ePROM platform is a beneficial tool that improves their outcomes. 112…”
Section: Future D Irec Ti On S For Re S E Archmentioning
confidence: 99%
“…If the same efforts are made to ensure trial follow-up measurements are more convenient for participants, then trials are equally expected to see improved retention. Patient self-assessment studies have produced reliable measurement in other fields of medicine despite initial hesitation and concern [30,31].…”
Section: Current Contextmentioning
confidence: 99%
“…7 PROMs can help healthcare professionals make informed decisions, foster effective communication with patients/families, monitor symptoms and the effectiveness of treatments and prioritize patient needs. 8 11 The most commonly used PROMs in palliative care are the Edmonton Symptom Assessment System (ESAS) 12 and the Integrated Palliative Care Outcome Scale (IPOS). 5 …”
Section: Introductionmentioning
confidence: 99%
“… 25 , 27 30 They gather symptom data such as anxiety, drowsiness, fatigue, nausea, and pain, enabling clinicians to prioritize patients’ needs based also on their questionnaire scores. 9 However, the integration of e-PROMs into oncological palliative care is challenged by a myriad of factors such as cultural and socioeconomic influences, familiarity with technological devices, 24 care settings, deteriorating functional health status 9 , 24 and emotional symptoms that are perceived as burdens and may even overshadow physical manifestations. 11 …”
Section: Introductionmentioning
confidence: 99%